Franchise agreements under EC competition law - İnanöz, Yetkin (My University, 2002)
The purpose of our study is to examine franchise agreements, which are widely used in the world of commerce, in respect of European Community Competition law and thus to reach conclusions concerning the use of franchise agreements in EC law. The method which was heavily used for researching on the subject was to benefit from the EC legislation concerning the application of EC competition rules to franchise agreements, the judgments of the European Court of Justice and the European Court of First Instance, the publications of the Community institutions and foreign and native books. The application of European Community Competition law to franchise agreements was first discussed in the Pronuptia case in 1986. Following the Pronuptia case, Block Exemption Regulation No.4087/ 88 on the application of EC competition rules to franchising was brought into force and it was applied until 2000. Ultimately, Regulation No.2790/ 99 was adopted by the European Commission. The subject of Regulation 2790/ 99 is the application of EC competition rules to vertical agreements which are concluded between the enterprises at different levels of production chain. Franchise agreements are covered by such Regulation as well. The Pronuptia judgment which is the first and the last judgment of the European Court of Justice regarding franchise agreements, five individual exemption applications to the European Commission following the Pronuptia judgment and five decisions of the Commission on such exemption applications, Regulation No.4087/ 88 and finally Regulation 2790/ 99 were comparatively examined in the thesis. Since the Pronuptia judgment, franchise agreements have been deemed to be pro-competitive in EC Competition law. Such an attitude was reflected on the legislation as well. Although Regulation 2790/ 99 generally reflects the same approach, the franchise world did not approve of the Regulation since it is a framework regulation on vertical agreements and since it does not clearly regulate franchise agreements compared to Regulation 4087/ 88, and they commented it as a regulation detrimental to franchise system. Regulation 2790/ 99, which is generally applied to vertical agreements, in my view, contains some uncertainties. In the drafting of agreements, due to such obscurity in Regulation 2790/ 99, different types of agreements may be preferred instead of franchise agreements and such a situation may cause some changes in the context of franchise agreements and the rate of their use in trade.

Avrupa Topluluğu Hukuku'nda Franchise Sözleşmeleri konulu çalışmamızın amacı uygulamada oldukça yaygın kullanılan franchise sözleşmelerini Avrupa Topluluğu Rekabet Hukuku kapsamında incelemek ve bu inceleme neticesinde franchise sözleşmelerinin Avrupa Topluluğu Hukuku'ndaki uygulama alanına dair tespitlerde bulunmaktır. Tezin hazırlanmasına yönelik araştırmalarda ağırlıklı olarak kullanılan yöntem, franchise sözleşmelerinin Avrupa Topluluğu Rekabet Hukuku kapsamında uygulanması konusundaki Avrupa Topluluğu mevzuatından, Avrupa Adalet Divanı ve Avrupa İlk Derece Mahkemesi kararlarından, Topluluk kurumları yayınlarından ve yerli ve yabancı eserlerden yararlanmaktır. Avrupa Topluluğu Rekabet Hukuku'nun franchise sözleşmelerine uygulanması konusu ilk kez 1986 yılındaki Pronuptia davası ile gündeme gelmiştir. Sonraki yıllarda Topluluk Rekabet Hukuku'nun franchise sözleşmelerine uygulanması konusunda 408788 sayılı Tüzük yürürlüğe girmiş ve bu Tüzük 2000 yılına kadar uygulanmıştır. En son olarak ise 279099 sayılı Tüzük yayınlanmıştır. Bu son Tüzüğün konusu, Topluluk Rekabet Hukuku'nun, üretim zincirinin farklı seviyelerindeki işletmeler arasında yapılan ve dikey anlaşmalar olarak bilinen anlaşma türlerine uygulanmasıdır ve franchise sözleşmeleri de bu Tüzük kapsamındadır. Tezin amacı doğrultusunda, franchise sözleşmelerini konu edinen ilk ve son Topluluk Mahkemesi kararı olan Pronuptia kararı, Pronuptia kararını takiben Avrupa Topluluğu Komisyonu'na Topluluk rekabet kurallarından muafiyet talebiyle yapılan beş başvuru ve bu başvuruların sonucu olan beş ayrı Komisyon Kararı, 408788 sayılı Tüzük ve de son olarak 279099 sayılı Tüzük karşılaştırmalı olarak detaylı bir biçimde incelenmiştir. Franchise sözleşmeleri Pronuptia kararından itibaren Topluluk bünyesindeki rekabet koşullarını iyileştirecek bir sözleşme türü olarak kabul edilmiştir. Bu anlayış ilgili mevzuata da yansımıştır. 279099 sayılı Tüzük de genel olarak bu anlayışı yansıtmakla beraber, genel çerçevede bir düzenleme olması ve önceki Tüzüğe oranla franchise sözleşmelerini açıkça düzenlememesi sebebiyle franchise dünyasında pek hoş karşılanmamış ve franchise sistemine zarar verecek bir düzenleme olarak yorumlanmıştır. Genel anlamda dikey anlaşmalara uygulanan 279099 sayılı Tüzük kanaatimce de franchise sözleşmeleri açısından belirsizlikler içermektedir. Franchise sözleşmelerinin hazırlanmasında, Tüzük'teki belirsizlikler sebebiyle franchise sözleşmeleri yerine başka sözleşme türlerinin tercih edilmesi söz konusu olabilecek ve bu durumda franchise sözleşmelerinin yapısında ve bu sözleşmelerin tercih edilme oranında değişiklikler meydana gelebilecektir.
Keywords: Avrupa Birliği_Hukuk